2012
DOI: 10.1007/s10934-012-9572-3
|View full text |Cite
|
Sign up to set email alerts
|

Potassium geopolymer foams made with silica fume pore forming agent for thermal insulation

Abstract: International audiencePorous potassium based geopolymers with a mutli-scale porosity were synthesized. Silica fume is introduced as an additive to the geopolymer formulation. The free silicon contained inside this silica fume is oxidized in alkaline solution, releasing molecular hydrogen which generates the porosity. Previous work has shown how the porosity can be controlled with temperature, repeated temperature cycles and the mass introduced. Using this protocol, homogeneous foams were made and then studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 23 publications
4
35
0
Order By: Relevance
“…Besides, Feng et al used a similar amount of H2O2 in a fly ash-based geopolymer, obtaining comparable results in terms of density and thermal conductivity (335 kg/cm 3 and 0.082 W/mK, respectively) and a slightly higher compressive strength of 0.96 MPa [33]. As previously discussed, in the material investigated here The thermal conductivity of the material, calculated as the average on three samples, was of 0.073 W/mK at 30 • C for an average bulk density of 313 kg/m 3 , a value in line with previous studies on alkali activated foams [18,32,33,38] and lower than other lightweight inorganic materials for thermal insulation such as aerated concrete [39,40]. As evidenced from many literature studies, the thermal conductivity of a porous material mainly relates with its density, a parameter which in turn is determined by different factors such as the solid/liquid ratio, the curing temperature, the addition of surfactants/foaming agents and the raw materials used [9,17,21,32,33].…”
Section: Thermal Propertiessupporting
confidence: 90%
“…Besides, Feng et al used a similar amount of H2O2 in a fly ash-based geopolymer, obtaining comparable results in terms of density and thermal conductivity (335 kg/cm 3 and 0.082 W/mK, respectively) and a slightly higher compressive strength of 0.96 MPa [33]. As previously discussed, in the material investigated here The thermal conductivity of the material, calculated as the average on three samples, was of 0.073 W/mK at 30 • C for an average bulk density of 313 kg/m 3 , a value in line with previous studies on alkali activated foams [18,32,33,38] and lower than other lightweight inorganic materials for thermal insulation such as aerated concrete [39,40]. As evidenced from many literature studies, the thermal conductivity of a porous material mainly relates with its density, a parameter which in turn is determined by different factors such as the solid/liquid ratio, the curing temperature, the addition of surfactants/foaming agents and the raw materials used [9,17,21,32,33].…”
Section: Thermal Propertiessupporting
confidence: 90%
“…In addition, according to Temuujin et al [98], geopolymers are capable of anti-ultraviolet and antiaging, which made them suitable as coating for exterior wall building to conserve energy. The studies on the thermal and fire performance of geopolymers have also been reported elsewhere [81,[99][100][101]. As mentioned earlier, geopolymers have molecular structures to resemble zeolitic materials.…”
Section: Applications Of Geopolymersmentioning
confidence: 89%
“…e main challenge on inorganic insulation materials' development is related to the production of a high porous material with sufficient mechanical properties. Geopolymer foams can be produced by the introduction of foaming agents such as hydrogen peroxide [18][19][20][21], metal powders [22][23][24], or silica fumes [25][26][27]. eir foaming action is due to the oxygen or hydrogen formation in alkaline conditions according to the following reactions:…”
Section: Introductionmentioning
confidence: 99%